The Effect of Auditory Icon on Food Intake Mimicry - Ismail, Suzilah; Baharin, Hanif; Yusof, Norhayati (International Journal of Psychosocial Rehabilitation, 2019)
Persuasive technology is very beneficial in inducing good human behaviour through mimicry, which is defined as imitating someone or something. Thus, in this study, an experiment is conducted to determine the effect of a fixed and natural rhythm auditory icon on food intake mimicry based on gender, eating phases (i.e., slow, moderate, & fast), and Wizard of Oz. Thirty males and thirty females are involved in four stages of the experiment. The first stage is implemented to screen their food intake patterns individually while eating an apple without listening to any sound. Next, they are categorised into three groups according to their natural eating phases: slow, moderate, or fast. Then, based on Wizard of Oz, they are divided into either yes or no conditions. In the second stage, a fixed rhythm auditory icon, which is represented by a sound of biting an apple for every ten seconds, is introduced while each participant is eating an apple during the experiment. Natural rhythm is embedded in the third and fourth stages, which are created from the natural eating phases of the participants in the first stage. Food intake mimicry is defined as eating that occurs within five seconds of hearing the fixed or natural rhythm auditory icon. ANOVA and repeated measures ANOVA were used to analyse the experimental data. Overall, the fixed rhythm auditory icon contributes to the highest food intake mimicry percentage of about 50% because the participants of the experiments can adapt to fixed rhythm much better than natural rhythm because they can anticipate when the fixed sounds are going to occur since it is fixed at 10 seconds. The main effect of gender, phase, and Wizard of Oz is not significant, but the interactions between them are significant (i.e., Gender & Phase and Phase & Wizard of Oz). These findings indicated that auditory icons can influence the eating phase, where eating slowly is good for health.